(untitled) (Research, Society and Development, 2023)
The objective of this research is to understand, from the perspective of scientific literacy, how the internet is used by 4th and 5th grade elementary school teachers, as a source of information to aid science teaching in a school in the state of Santa Catarina. The work is characterized as descriptive, with a qualitative approach to the problem. The research strategy is the case study, whose sources of evidence for the triangulation are: contextualization of the school, interviews with teachers, teaching plans and classroom activities. The results show that indications of the internet as a source of information intensified during the period of the Covid-19 pandemic (year 2020), a school year in which classes were intermediated by technology. It is noticed that the teachers have a basic understanding of fundamental scientific terms, knowledge and concepts. However, some gaps are evident, mainly with regard to understanding the nature of science and understanding the existing relationships between science, technology, society and the environment, which implies the pedagogical work of teachers. It is apparent that teachers, in their initial (academic), complementary and continuing training, are concerned with training themselves, with the support of the HEI, but, with regard to scientific literacy, there is no record of this training. It is concluded that, in this study, gaps are apparent in terms of teacher training in terms of scientific literacy, research, use of sources and scientific rigor.